Qualidade de vida no trabalho : um estudo no setor de ferragens da Cooperativa Tritícola de Espumoso - COTRIEL - Matos, Jardel da Silva de (2017)
This study demonstrates the importance of the topic Quality of Life at Work in people management within organizations, since it is where people spend most of their lives. It presents as a general objective to analyze how the employees of the hardware sector of the Cooperativa Tritícola de Espumoso-COTRIEL perceive the QVT and, as specific objectives, to describe the actions developed by the cooperative in relation to the QVT in the hardware sector, to know the perception of the employees of the sector as for the QWL programs, raise their opinions on the aspects that can influence the improvement of the QWL and suggest proposals for improvements for the hardware sector, with a view to making the work environment more pleasant. The methodology used in the research is classified as a descriptive and exploratory research, of a qualitative nature, with the purpose of a study of formative evaluation and technical procedure of survey research. The data collection instrument was a questionnaire with 35 closed questions based on Richard Walton's quality of life model, complemented by 2 open questions. At the end of this research it was found that, in a comprehensive way, the QWL programs of the cooperative, which are applied in the hardware sector, are satisfactory, however, in some aspects, it was observed that they need restructuring and improvements. Therefore, it was suggested the restructuring of positions and salaries, the improvement of well-being and acclimatization of the work environment, of extra benefits and also health and dental plans, as well as better supervision of work and integration of employees.